Long-term In-Vivo Tumorigenic Assessment of Human Culture-expanded Adipose Stromal/Stem Cells - MacIsaac, Zoe Marie (2011)
After more than a decade of extensive experimentation, the promise of stem cells to revolutionize the field of medicine has negotiated their entry into clinical trial. Adipose tissue specifically holds potential as an attainable and abundant source of stem cells. Currently undergoing investigation are adipose stem cell (ASC) therapies for diabetes and critical limb ischemia, among others. In the enthusiastic pursuit of regenerative therapies, however, questions remain regarding ASC persistence and migration, and, importantly, their safety and potential for neoplasia. To date, assays of in vivo ASC activity have been limited by early end points. We hypothesized that with time, ASCs injected subcutaneously undergo removal by normal tissue turnover and homeostasis, and by the host’s immune system. In this study, a high dose of culture expanded ASCs were formulated and implanted as multicellular aggregates into immunocompromised mice, which were maintained for over one year. Animals were monitored for toxicity, and surviving cells quantified at study endpoint. No difference in growth/weight or lifespan was found between cell-treated and vehicle treated animals, and no malignancies were detected in treated animals. Moreover, real-time PCR for a human specific sequence, ERV-3, detected no persistent ASCs. With the advent of clinical application, clarification of currently enigmatic stem cell properties has become imperative. Our study represents the longest duration determination of stem cell activity in vivo, and contributes strong evidence in support of the safety of adipose derived stem cell applications.